A New Algorithm for Protection of Small Scale Synchronous Generators Against Transient Instability - Zinat Khosravi; Alireza Saffarian (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Today, installation of small generators has been increased because of their considerable benefits in distribution systems in distributed generation. One of the most important problems for transient stability is the effects of the faults of system. Small scale generators have low constant inertia and protection relays have slow performance in distribution systems. Therefore transient instability is a probable phenomenon for the systems with these generators. In this paper, dynamic response of generator has been studied in different fault conditions and then by introducing the concept of " critical fault clearing time ", the sensitivity of this time to the fault type and also fault location parameters have been studied. Then a new protection scheme has been proposed to prevent of transient instability for small scale generator. This protection scheme uses a new evolutionary algorithm based on the active power of generator and critical fault clearing time. The proposed relay can prevent of wrong and unwanted performance. Furthermore it can disconnect the generator from the system in three phase fault near of the bus-bar before its instability. Simulation results show reliable performance of the proposed relay against system transients.